Comparative Biochemical Investigations of Over Doze Diazepam in Albino Rats. An Experimental Forensic Study - Muhammad Rashid, Mohsana Urooj Rana, Amna Shahid, Azra Anwar, Muhammad Ikram Ali, Alina Saqib, Javed Anver Qureshi, Naveed Shuja, Arslan Shuja (Pakistan Journal of Medical & Health Sciences, 2023)
Methodology: Total 20 male albino Rats of approximately 100 gm of weight were selected and divided them into four different groups. In Group A, 5 individuals were control while in group B, group C and group D, there were 5 rats in each group and they were treated orally with 0.2mg/kg, 03mg/kg and 0.4mg/kg Diazepam respectively. Blood pH, serum Creatinine, serum Bicarbonate serum ALT and AST levels were measured after 10, 20 and 30 days of intervals of time. Blood sample were collected from tail in container after centrifugation.